2009
DOI: 10.1007/s00467-009-1138-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of idiopathic steroid-resistant nephrotic syndrome: a multicenter study

Abstract: Long-term outcome of idiopathic steroid-resistant nephrotic syndrome was retrospectively studied in 78 children in eight centers for the past 20 years. Median age at onset was 4.4 years (1.1-15.0 years) and the gender ratio was 1.4. Median follow-up period was 7.7 years (1.0-19.7 years). The disease in 45 patients (58%) was initially not steroid-responsive and in 33 (42%) it was later non-responsive. The main therapeutic strategies included administration of ciclosporine (CsA) alone (n = 29; 37%) and CsA + myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
133
5
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(167 citation statements)
references
References 34 publications
15
133
5
14
Order By: Relevance
“…3 In early childhood, INS is two times more frequent in boys than in girls, but this balance is disrupted in adolescence affecting both girls and boys equally. Mekahli et al 4 found the ratio between boys and girls to be 1.4/1 and it was 1.5/1 in our study. The age of disease onset is usually towards two years; and the majority of the children are under the age of 6 years.…”
Section: Discussionsupporting
confidence: 61%
“…3 In early childhood, INS is two times more frequent in boys than in girls, but this balance is disrupted in adolescence affecting both girls and boys equally. Mekahli et al 4 found the ratio between boys and girls to be 1.4/1 and it was 1.5/1 in our study. The age of disease onset is usually towards two years; and the majority of the children are under the age of 6 years.…”
Section: Discussionsupporting
confidence: 61%
“…Steroid-resistant nephrotic syndrome (SRNS) is a challenging clinical condition with highly variable outcomes, and 50% of children progress to ESRD within 15 years (3,4). Although in some patients, temporary or persistent remission is achieved by intensified immunosuppressive therapies (IITs), others exhibit a multidrug-resistant phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of steroid-resistant nephrotic syndrome (SRNS) is poor, with a high proportion of patients rapidly developing end-stage renal disease, requiring dialysis or transplantation (1,2). The GFB is comprised principally of podocytes, specialised epithelial cells which interdigitate at junctions known as slit diaphragms (SDs).…”
mentioning
confidence: 99%